Assessment of corrosive attack of Fe9Cr1Mo alloys in pressurised CO2 for prediction of breakaway oxidation - Gong, Yilun; Gill, Simon P. A.; Yan, Sabrina; Higginson, Rebecca; Sumner, Joy; Simms, Nigel J.; Larsson, Henrik; Shin, Aya; Pearson, Jonathan M.; Young, David J.; Atkinson, Colin; Cocks, Alan C. F.; et al. (Elsevier, 2023)
To provide clarity on the poorly-understood mechanism of breakaway oxidation, corrosion of Fe9Cr1Mo steel in pressurised CO is quantified and modelled. The temperature range 400–640 , relevant to nuclear power plants, is emphasised. Attack is in the form of combined oxide scale growth and internal carburisation of the metal. Carbon activity in the metal at its surface exhibits a strong time dependence consistent with the kinetically-limited transport of carbon due to the slow Boudouard reaction. Breakaway is associated with the approach to saturation of the steel with respect to carbon. Diffusion modelling agrees well with steel carbide precipitation observations.
Keywords: Oxidation; Carburisation; Breakaway; Modelling; Characterisation; Lifing